Endoreplication and polyploidy: insights into development and disease - Fox, Donald T. (Company of Biologists, 2013)
Polyploid cells have genomes that contain multiples of the typical diploid chromosome number and are found in many different organisms. Studies in a variety of animal and plant developmental systems have revealed evolutionarily conserved mechanisms that control the generation of polyploidy and have recently begun to provide clues to its physiological function. These studies demonstrate that cellular polyploidy plays important roles during normal development and also contributes to human disease, particularly cancer.